Factor XIII Val34Leu polymorphism and the risk of myocardial infarction under the age of 36 years - Rallidis, Loukianos S.; Politou, Marianna; Komporozos, Christoforos; Panagiotakos, Demosthenes B.; Belessi, Chrisoula I.; Travlou, Anthi; Lekakis, John; Kremastinos, Dimitrios T. (Thrombosis and Haemostasis, 2008)
There are limited and controversial data regarding the impact of factor XIII (FXIII) Val34Leu polymorphism in the pathogenesis of premature myocardial infarction (MI). We examined whether FXIII Val34Leu polymorphism is associated with the development of early MI.We recruited 159 consecutive patients who had survived their first acute MI under the age of 36 years (mean age=32.1 ± 3.6 years, 138 were men). The control group consisted of 121 healthy individuals matched with cases for age and sex, without a family history of premature coronary heart disease (CHD). FXIII Val34Leu polymorphism was tested with polymerase chain reaction and reverse hybridization. There was a lower prevalence of carriers of the Leu34 allele in patients than in controls (30.2 vs. 47.1%, p=0.006). FXIII Val34Leu polymorphism was associated with lower risk for acute MI after adjusting for major cardiovascular risk factors (odds ratio [OR] = 0.51, 95% confidence interval [CI] 0.27–0.95, p=0.03). Subgroup analysis according to angiographic findings (“normal” coronary arteries [n=29] or significant CHD [n=130]) showed that only patients with MI and significant CHD had lower prevalence of carriers of the Leu34 allele compared to controls after adjusting for major cardiovascular risk factors (OR = 0.42, 95% CI 0.22–0.83, p=0.01). Our data indicate that FXIII Val34Leu polymorphism has a protective effect against the development of MI under the age of 36 years, particularly in the setting of significant CHD.
Keywords: Factor XIII Val34Leu polymorphism; premature myocardial infarction; risk factors